DETERMINATIONS ON THE STRUCTURE OF VERB CONJUGATION IN TURKISH - Mehmet Turgut BERBERCAN (Fırat University, 2019)
In this article, how the verb conjugation is made and its structural features and functional areas in use are analysed via the examples selected from historical and modern Turkish dialects. In terms of morphological, syntactical and morphotactical functions of the establisher of the verb conjugation, the basic auxiliary verb er– (> ér–, é–, e–, i–), are examined by propounding various determinations on the general principles of the verb conjugation which has two varieties as simple and complex conjugation. In addition the structural complexion of the usings in which the auxiliary verb dropped is determined through the examples selected from the texts from Old and Middle Turkic texts.